Diet, Lifestyle and Chronic Widespread Pain: Results from the 1958 British Birth Cohort Study - Elizabeth G VanDenKerkhof; Helen M Macdonald; Gareth T Jones; Chris Power; Gary J Macfarlane (Pain Research and Management)
OBJECTIVES: To examine the relationship between diet and lifestyle, and chronic widespread pain (CWP). If persons with CWP have dietary and lifestyle habits consistent with an increased risk of cancer or cardiovascular disease, it may partially explain evidence in the literature suggesting an association between CWP and these diseases.